The Identification of Public Values on the Winning-Public Service Innovations: Case Study of the United Nations Public Service Awards Winner in 2015-2024 - Muhammad Nura Kallyndra (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although public value and public service innovation have received substantial attention in public administration research, limited scholarship has systematically examined the public values embedded in internationally recognized service innovations. This study aimed to identify and synthesize the public values reflected in innovations recognized by the United Nations Public Service Awards (UNPSA) between 2015 and 2024 and to develop a comprehensive Public Values Framework. A qualitative descriptive approach with a multiple-case study design was employed, involving 97 UNPSA award-winning public service innovations selected through purposive sampling. Data were collected from official UNPSA documents, government reports, and relevant scholarly publications using a structured document analysis protocol. Document analysis was integrated with thematic analysis following Braun and Clarke’s six-stage framework, while data-source triangulation was used to enhance the credibility of the findings. The analysis identified four major dimensions of public value: Outcome Achievement, Trust and Legitimacy, Service Delivery Quality, and Efficiency. Across these dimensions, Fairness, Equity, Adaptability, Stakeholder Value, Innovation, and Citizens’ Involvement emerged as the most prominent values. The findings demonstrate that successful public service innovations create public value not only by improving administrative performance but also by promoting inclusive governance, citizen participation, organizational adaptability, and collaborative stakeholder engagement. This study advances Public Value Theory by integrating innovation typology with multidimensional public value analysis and by proposing a comprehensive framework for examining value creation in public service innovation. Practically, the framework provides governments and public managers with guidance for designing and evaluating citizen-centered innovations and establishes a foundation for future comparative and mixed-methods research on public value creation.